2021
DOI: 10.3389/fmicb.2021.681474
|View full text |Cite
|
Sign up to set email alerts
|

The Persistent Challenge of Pneumocystis Growth Outside the Mammalian Lung: Past and Future Approaches

Abstract: The pathogenic fungi in the genus, Pneumocystis, have eluded attempts to continuously grow them in an ex vivo cultivation system. New data from transcriptomic and genomic sequencing studies have identified a myriad of absent metabolic pathways, helping to define their host obligate nature. These nutrients, factors, and co-factors are acquired from their mammalian host and provide clues to further supplementation of existing media formulations. Likewise, a new appreciation of the pivotal role for the sexual cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…In light of the findings that Pneumocystis spp. has a significantly reduced genome size and lacks many crucial biosynthetic pathways required to survive outside of the host [4], it is currently accepted that this pathogen is an obligate biotroph [45][46][47][48][49], depending on the host lungs for nutrients. Yet, this study demonstrated that P. suis is able to cope with several co-infecting agents at the same time, even though this might not be valid for an extended period of time, thus explaining its decreased prevalence at four months.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the findings that Pneumocystis spp. has a significantly reduced genome size and lacks many crucial biosynthetic pathways required to survive outside of the host [4], it is currently accepted that this pathogen is an obligate biotroph [45][46][47][48][49], depending on the host lungs for nutrients. Yet, this study demonstrated that P. suis is able to cope with several co-infecting agents at the same time, even though this might not be valid for an extended period of time, thus explaining its decreased prevalence at four months.…”
Section: Discussionmentioning
confidence: 99%
“…This impedes the development of better treatment options, understanding drug interactions particularly with ART, and in vitro assays that would clarify host/pathogen interactions. Recently discussed by Cushion et al, finding new approaches to identify a viable culture system for Pneumocystis would revolutionize the approach to combating PCP 71 . Now that the genome has been published important information is available on how Pneumocystis uses host factors for survival 62 .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Despite its major impact upon human health, we remain remarkably ignorant about the biology and epidemiology of Pneumocystis . The inability to culture Pneumocystis in vitro , despite 3 decades of research, makes this pathogen uniquely difficult to study ( 9 ). The lack of in vitro culture methods also delayed the generation of full genome sequences, further slowing research on the Pneumocystis genus.…”
Section: Introductionmentioning
confidence: 99%
“…These have highlighted, for example, the importance of metabolic adaptation, micronutrient assimilation, and stress responses for the establishment of infections by Candida albicans , Cryptococcus neoformans , and Aspergillus fumigatus ( 21 24 ). It is not yet possible to culture Pneumocystis in vitro ( 9 ). Therefore, using bioinformatic approaches, we have explored more deeply the evolution of a range of families of transcriptional regulators in Pneumocystis to gain further insights into the reduced biology of these pathogens.…”
Section: Introductionmentioning
confidence: 99%